Connective action and the echo chamber of ideology: Testing a model of social media use and attitudes toward the role of government. Issue 1 (2nd January 2017) - Ingrams, Alex
ABSTRACT: Scholars continue to debate how information and communications technology (ICT) influences civic behavior. Existing studies may be grouped into two approaches: ICT as a tool used to achieve a civic end, and ICT as an unanticipated influencer of how citizens view civic roles. This paper develops the second theory by testing moderated relationships between social media use, political identity, and citizen views of government service provision and spending. Regression results suggest that liberal users show greater preference for an active government, while conservatives show less preference.